THE IMPLEMENTATION OF ‘GUIDED INQUIRY MODEL’ ON PHYSICS LEARNING IN THE 3RD GRADE STUDENTS OF SCIENCE I SMAN 1 PURWOHARJO 2013/2014 - Marsiyah - (saintifika, 2014)
Physics is one of the lessons that the students do not like the most, so it results in students learning activities which then will lead to the low interest of the learning itself. The result of the observation during the learning process in the 3rd grade students of science I showed that there were only six students who actively raised their hands and asked some questions, while 65% of them followed the class regularly. The questionnaires confirmed that only 45% of them who liked physics, so it resulted in the result of their study on physics that was low, and only 45% of them who finished studying physics. Therefore, this research was conducted by applying ‘guided inquiry’ model on physics learning in the 3rd grade students of science I at the first semester of 2013/2014. The indicators used to measure the effectivity of the learning process were students learning activities, students learning goals, and students perception on the learning itself.The result in cycle 1 showed that the average of the students activities reached 65%, the students learning goals reached 65%. It was related to the number of the students who liked physics turned into 65%. Moreover, cycle 2 showed that there was the increasing number of the students learning activities that had reached 75%, the students learning goals had also reached 75%, and those who liked physics had reached 70%. Based on the result noted above, it can be drawn the conclusion that the implementation of ‘guided inquiry’ model can effectively improve the students learning activities and their learning goals as the result of the increasing number of the students who like physics.